Effects of lorcaserin on cardiometabolic risk factors in overweight and obese patients: A systematic review and meta‐analysis - Kuo, Hsiao‐Huai; Wang, Kuang‐Te; Lee, Ying‐Hsiang; Lin, Po‐Lin; Liu, Ming‐En; Lin, Chien‐Yu; Liu, Lawrence Yu‐Min (Journal of clinical pharmacy and therapeutics, 2020)
What is known and objective Lorcaserin is a selective serotonin 2c receptor agonist approved as an anti‐obesity agent. The additional cardiometabolic benefits associated with lorcaserin have not been conclusively established. The aim of the systematic review and meta‐analysis is to examine the effects of lorcaserin on blood pressure, heart rate and other metabolic parameters in overweight and obese patients from randomized controlled clinical trials (RCTs). Methods A literature search was conducted on PubMed, EMBASE and Cochrane Central using the search terms ‘lorcaserin’ and ‘randomized controlled trials’ without language restrictions. RCTs with a follow‐up period of at least 24 weeks were included in the meta‐analysis. Results and discussion Six studies with 9452 patients in the lorcaserin group and 9392 patients in the placebo group were included. Compared with placebo, lorcaserin not only reduced weight, BMI and waist circumference but also improved SBP, DBP, heart rate, LDL, triglycerides, fasting plasma glucose and HbA1c. Our findings suggest that lorcaserin has trivial though consistent and favourable effects on blood pressure, heart rate and metabolic syndrome. What is new and conclusion Lorcaserin improved all cardiometabolic parameters modestly in addition to its weight loss effect in overweight and obese patients. More research is needed to determine its long‐term cardiovascular benefits. This meta‐analysis of 6 randomized controlled trials showed that lorcaserin has trivial though consistent and favorable effects on all cardiometabolic parameters in addition to its weight loss effect in overweight and obese patients.